The Relationship Between Pregnant Women’s Perceptions Of Family Support And The Motivation For HIV/AIDS Examination In Gedong Tengen Public Health Center. Yogyakarta City - Maria Wiwin I.H. Lende; Setyo Mahanani Nugroho; Nonik Ayu Wantini (Alma Ata University Press, 2018)
In 2016 the number of pregnant woman who required the prevention of transmission trough sexual reached 278 pregnant women. Efforts that have been made by government to prevent mother-to-child transmission of HIV/AIDS are HIV/AIDS comprehensive service which are sustainable that cover all froms of services for HIV and sexual transmitted infections. In 2015, the lowest coverage of HIV/AIDS examination in Yogyakarta City was at Gedong Tengen Public Health Center, which was 3,7%. In addition to medical efforts, pregnant women need psychological and social support from people around the family and surronding environment, and motivation to have HIV/AIDS examinations. The purpose of study is to find out the relationship between pregnant women’s perceptions of family support and the motivation for the HIV/AIDS examination in Gedong Tengen Public Health Center, Yogyakarta City. The study used the analytical descriptive method with the cross-sectional design. The research population comprised 48 pregnant women and the sampel consisted of 43 pregnant women. The sampling thecnique was accidental sampling technique. The data analysis in the study used Kendall tau. The results of the data analysis showed thats most of the pregnat women were 20-35 years old (86%), had secondary education (60.5%), unemployed (74.4%), and were multiparae (62.8%). Perceptions of family support were negative (58.1%), and their motivation for the HIV/AIDS examination was moderate (72.1%). The result of the analysis using Kendall tau test showed p-value = 0.001 and z table = 4.35. There is relationship between pregnant women’s perceptions of family support and the motivation for the HIV/AIDS examination in Gedong Tengen Public Health Center, Yogyakarta City. Keywords: Perceptions; motivation; HIV/AIDS